Single-molecule tracking measurement of PDMS layer during curing process - Iwao, Ryo; Yamaguchi, Hiroki; Niimi, Tomohide; Matsuda, Yu (Physica A, 2021)
The curing process of poly(dimethylsiloxane) (PDMS) was microscopically investigated by the single-molecule tracking method based on the diffusion motion of fluorescent dye molecules adding to the PDMS layer stored at a temperature of 308K. The PDMS layer was completely cured at 900 min after adding a curing agent. We compared the time- and ensemble-averaged mean square displacements (MSDs) of the tracked molecules at 90, 510, and 900 min after adding the curing agent into the PDMS layer. The discrepancies were observed between the time- and ensemble-averaged MSDs, indicating weak ergodicity breaking. The spatially averaged diffusion coefficient exhibited a two-step decrease: first step was rapid decrease suggesting the extent of crosslinking, and second step was slow one suggesting the increase of crosslink density. The single-molecule trajectory scale analysis revealed the heterogeneous distribution of the diffusion coefficient. By calculating the heat map from the slope of moment scaling spectrum (MSS) of each single-molecule trajectory, cluster structures were recognized. The spatial correlation of the slope of MSS decreased with the time elapsed. These results suggested the existence of the heterogeneous structure in the PDMS layer during the curing process. •The curing process of poly(dimethylsiloxene) (PDMS) was microscopically investigated by the single-molecule tracking (SMT) method.•The weak ergodicity breaking was observed.•Both normal and confined diffusions were observed in the PDMS layer during the curing process.